2018
DOI: 10.17221/8/2017-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Associations between gene polymorphisms, breeding values, and glucose tolerance test parameters in German Holstein sires

Abstract: The association between several gene polymorphisms, the estimated breeding values for milk performance traits, and glucose metabolism measured by the glucose tolerance test (GTT) in German Holstein sires were evaluated. Polymorphisms in DGAT1, GH1, GHR, FASN, and OLR1 genes were not associated with the GTT. A significant relationship was obtained for the DGAT1 AA/GC polymorphism and estimated breeding values for milk performance (milk yield, fat and protein yield, fat and protein percentage). The polymorphism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Additionally, when the effects of alleles are evaluated, A is advantageous but not significantly so ( Table 2 ). This result is generally in agreement with previous findings and confirms our previous finding in German Holsteins regarding the trend of increasing frequency of the alanine variant [ 32 , 33 ].…”
Section: Resultssupporting
confidence: 93%
“…Additionally, when the effects of alleles are evaluated, A is advantageous but not significantly so ( Table 2 ). This result is generally in agreement with previous findings and confirms our previous finding in German Holsteins regarding the trend of increasing frequency of the alanine variant [ 32 , 33 ].…”
Section: Resultssupporting
confidence: 93%
“…Somewhat surprisingly, the DGAT1 polymorphism did not show such an influence; the AA genotype was superior to AK only in C22:0 ( p < 0.05) and AK over AA in C20:4n-3 ( p < 0.01). The influence of DGAT1 gene polymorphisms on the fat content in cow´s milk has been confirmed repeatedly [ 18 , 19 , 28 ]. Other authors found that polymorphisms strongly influenced MCFAs and UFAs in DGAT1 and SCD1 .…”
Section: Resultsmentioning
confidence: 95%
“…The authors suggest that some of them could be useful as a marker selection for FA composition in milk. Specifically, DGAT1 (acyl-CoA diacylglycerol transferase 1) and SCD1 polymorphisms have recently become the focus [ 6 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Park et al investigated the genetic architecture of these traits and reported that the traits had moderate and high heritability estimates [ 22 ]. The previous studies on the association between genotypes and BVs considered BVs estimates of all additive genetic effects without the other environmental effects—and no environmental factor was included in the model [ 23 , 24 ]. Therefore, we followed their approaches in the association analysis for MAE SNPs.…”
Section: Methodsmentioning
confidence: 99%